A mixed methods assessment of the barriers and readiness for meeting the SNAP depth of stock requirements in Baltimore's small food stores. Issue 2 (4th March 2018) - Ross, Alexandra; Krishnan, Nandita; Ruggiero, Cara; Kerrigan, Deanna; Gittelsohn, Joel
ABSTRACT: We sought to understand Baltimore corner store owners' awareness of and readiness for the then-approved Supplemental Nutrition Assistance Program depth of stock requirements and assess potential barriers and solutions. In-depth interviews and stocking observations were conducted in 17 corner stores in low-income food deserts of Baltimore City. Corner store owners conveyed little to no awareness of the pending depth of stock changes. Only two stores were currently ready for the requirements. Low customer demand, high amounts of potential spoilage, and unfair pricing at the wholesaler were identified by store owners as barriers to stocking required foods.